2016
DOI: 10.1088/0953-8984/28/8/085601
|View full text |Cite
|
Sign up to set email alerts
|

Optical conductivity of layered calcium cobaltate Ca3Co4O9

Abstract: We report the optical properties of layered calcium cobaltate, Ca3Co4O9, which is regarded as a promising candidate for use as a thermoelectric material. The optical conductivity shows three broad peaks related to the inter-band transition below 4 eV, which are quite similar to those in the spectra of Na x CoO2. This similarity implies that the CoO2 layer, which is an essential unit for both Ca3Co4O9 and Na x CoO2, is dominant in the energy band structure below 4 eV. In addition, we estimate the effective carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
3
6
0
Order By: Relevance
“…13,48 Absorption peaks at similar wavelengths as reported here have been attributed to charge transfer transition between the O 2− and Co 3+ ions, 48 and the transition between the crystal-field splitted t 2g and e g Co 3d bands. 49 This is consistent with the observations made by Chambrier et al, 50 who observed an absorption onset at similar wavelengths for their Ca 3 Co 4 O 9 films fabricated with PLD.…”
Section: Resultssupporting
confidence: 92%
“…13,48 Absorption peaks at similar wavelengths as reported here have been attributed to charge transfer transition between the O 2− and Co 3+ ions, 48 and the transition between the crystal-field splitted t 2g and e g Co 3d bands. 49 This is consistent with the observations made by Chambrier et al, 50 who observed an absorption onset at similar wavelengths for their Ca 3 Co 4 O 9 films fabricated with PLD.…”
Section: Resultssupporting
confidence: 92%
“…Ca 3 Co 4 O 9 consists of alternate stacking of two types of layered subsystems with different b-axis parameter ( Fig. 1) [7]: The CdI 2 -type CoO 2 layer responsible for the charge transport and the rocksalt-type Ca 2 CoO 3 layer which behaves as the charge reservoir to supply holes into the CoO 2 layer [8][9][10][11]. The anomalous charge transport of this compound is clearly seen in the non-monotonic temperature variations of the electrical resistivity and the Seebeck coefficient [7,[12][13][14][15], but an underlying origin for these behaviors remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This compound consists of two subsystems of CdI 2 -type CoO 2 and rocksalt-type Ca 2 CoO 3 layers, alternately stacked along the c axis [1,2]. The former is responsible for the charge transport and the latter behaves as the charge reservoir to supply holes into the conduction layer [3][4][5][6]. As is distinct from other layered systems such as the high-T c cuprates, these subsystems have different b axis parameters (b 1 being for the rocksalt and b 2 for the CoO 2 layers).…”
Section: Introductionmentioning
confidence: 99%